Horticultural export quality explained - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Manual for horticultural export quality assurance by the Natural Resources Institute, 1994 ISBN 0 85954 382 X Natural Resources Institute Central Avenue, Chatham Maritime, Kent ME4 4RB, UK